HOUSe-KEEPER, A Vendor-independent Architecture for Easy Management of Smart Homes - Seigneur, Jean-Marc (Trinity College Dublin. Department of Computer Science, 2001)
Home-networking is gaining momentum. In a couple of months, Windows XP will be launched with the connected home experience as one of its core areas of interest. In the medium term at least, there will be more than one home networking "middleware" in a smart home, a home populated with smart, e.g., Web-enabled or network-enabled, devices. Nevertheless, the home system will have to present a global and complete view of smart devices in the home without excluding devices from one or more different high-level home networking technologies. HOUSe-KEEPER proposes an open architecture into which home networking "middleware" can be "plugged". In addition to being independent of the underlying highlevel home networking technologies, it provides a means to monitor and control smart devices remotely over the Internet, as well as to easily grant access control and add some context information to them. These features are still in development for the two main highlevel home networking technologies, Jini and UPnP. Moreover, HOUSe-KEEPER offers a real prototype of a smart home network accessible from the Internet for residential end-users. A lamp can be switched on from a Web page or the kettle for coffee water can be turned on from a WAP phone. The prototype demonstrates how it is possible to address the requirements of a smart home system thanks to the HOUSe-KEEPER architecture. The beginning of this document presents the domain of home-networking and its state of the art review. Then, the HOUSe-KEEPER architecture is described. Finally, there is an analysis of what has been achieved and what has been brought to light.
Keywords: Computer Science